Pemanfaatan Blog Sebagai Media Digital Marketing Untuk Meningkatkan Branding dan Promosi UMKM AR_FLORIST Diera Digital - Ningrum, Nurmah; Nada Alifia; Novadilastri; Sularno, Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The development of digital technology has created new opportunities for micro, small, and medium enterprises (MSMEs) to expand their markets and enhance competitiveness. AR_FLORIST is an MSME engaged in the floral board service sector, established in July 2025 in Padang City by owner Loli Ferbrina. The products offered include rustic floral boards and flowerbox boards with various themes tailored to customer requests. This study aims to analyze the utilization of blogs as a digital marketing medium to enhance the branding and promotion of AR_FLORIST. The research employed a descriptive qualitative approach through observation, interviews, and documentation. The results show that blogs can increase brand awareness, strengthen business image, and broaden promotional reach through creative content. Therefore, blogs serve as a strategic tool in supporting digital marketing for AR_FLORIST amid today’s competitive business environment.